2017
DOI: 10.1038/s41533-017-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of GP, nurse and practice manager views on using targeted case-finding to identify patients with COPD in primary care

Abstract: ‘Finding the missing millions’ with chronic obstructive pulmonary disease became part of the Department of Health strategy for England in 2010. Targeted case-finding within primary care is one potential pro-active strategy, but currently little is known about the views of healthcare professionals on this approach. In this study, 36 healthcare professionals (12 GPs, 14 nurses, and 10 practice managers) from 34 UK practices participated in semi-structured telephone interviews about targeted case-finding. Intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Exploration of the views of health care professionals involved in the case-finding trial highlighted limited capacity, resources, and expertise among primary care practitioners as potential explanations for this delay. 18 A more recent UK study by Summers et al 19 found that although health care professionals implementing targeted case-finding in primary care agreed that diagnosing COPD earlier had benefits, patients’ increased stress and negative responses added more strain on limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Exploration of the views of health care professionals involved in the case-finding trial highlighted limited capacity, resources, and expertise among primary care practitioners as potential explanations for this delay. 18 A more recent UK study by Summers et al 19 found that although health care professionals implementing targeted case-finding in primary care agreed that diagnosing COPD earlier had benefits, patients’ increased stress and negative responses added more strain on limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Ten yearly systematic active case-finding was the most cost-effective screening interval, although policymakers need to balance this against a greater proportion of the cohort remaining undiagnosed for longer and the value patients and practitioners place on early diagnosis 38…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, addressing potential barriers, challenges and concerns to patient uptake in GP may aid future case-finding implementation strategies. To date, only one research paper has explored the perceptions and experiences of patients attending a case-finding clinic while others have focussed on the views of health care professionals 26 28 .…”
Section: Introductionmentioning
confidence: 99%